Teeth Mobility Cause and Management of Mobile Teeth in Dental Clinic (Indian Journal of Forensic Medicine & Toxicology, 2020)
By examining firm pressure with two metal instruments on teeth, the extent of vertical and horizontaldisplacement considered as tooth mobility, which is due to either periodontal disease or trauma. Nowadaysteeth mobility is a common problem in dental scenarios, which results inocclusal problems, Dietaryproblems, and disturbances in mastication, aesthetic problem and worsening life quality. The treatment oftooth mobility is based on its etiology; it may be surgical or non-surgical. Surgically by Periodontal surgery,non-surgically by occlusal adjustment and splinting. Sometimes the Occlusal adjustment can be done by thesurgical process. In the article, we discuss the cause of tooth mobility, relation between tooth mobility andocclusion including indication, contraindication and principles of tooth splinting. Our ultimate goal is torestore mastication function, good aesthetic, to improve patient comfort and good oral functions by variousperiodontal treatments for the management of mobile teeth.
Keywords: Teeth Mobility, Adjustment Occlusion, Periodontal Splinting, Trauma of Periodontium, Types of Splinting.